Surface‐enhanced Raman spectroscopy is an accurate technique in diagnosis of breast cancer: A meta‐analysis. (23rd August 2022) - Yue, Xiang; Wang, Yashan; Guo, Dingjie; He, Guangliang; Sui, Chuanying; Qu, Zihan; Zhao, Yinlong; Liu, Xin
Abstract: The meta‐analysis was prepared to evaluate the diagnostic value of surface‐enhanced Raman spectroscopy for patients with breast cancer and to provide some statistically significant reference for the detection process. PubMed, Web of Science, Cochrane library, and Embase databases were retrieved for randomized clinical trials by two independent reviewers. A comprehensive search was performed on July 15, 2022. Meta‐Disc 1.4 was used to calculate Spearman correlation coefficient. STATA 14.1 software was used to evaluate the diagnostic effect and the performance of subgroup analysis, which could be conducted to explore the potential sources of heterogeneity. Review manager 5.3 software was performed for quality assessment in our meta‐analysis. The results displayed 19 studies with 1299 patients were included according to the inclusion and exclusion criteria. Meta‐analysis displayed the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio and the area under the curve of using surface enhanced Raman spectroscopy for diagnosing the patients with breast cancer were 0.91 (95% CI 0.85–0.94), 0.94 (95% CI 0.91–0.96), 14.06 (95% CI 9.25–21.35), 0.10 (95% CI 0.06–0.17), 140.64 (95% CI 59.63–331.70), and 0.97 (95% CI 0.95–0.98), respectively. The source of specificity heterogeneity was from different sample volume mixed with nanoparticle. Surface‐enhanced Raman spectroscopy had high sensitivity and specificity in the diagnosis of breast cancer. It was an accurate and effective technique for patients with breast cancer. Abstract : Surface‐enhanced Raman spectroscopy had high sensitivity and specificity in the diagnosis of breast cancer. In the detection process, the diagnosis performance was higher when the test sample was serum and the laser wavelength was 785 nm.